Alkyl polyglucoside vs. ethoxylated surfactant-based microemulsions as vehicles for two poorly water-soluble drugs: physicochemical characterization and in vivo skin performance - Pajić Nataša Z. Bubić; Todosijević Marija N.; Vuleta Gordana M.; Cekić Nebojša D.; Dobričić Vladimir D.; Vučen Sonja R.; Čalija Bojan R.; Lukić Milica Ž.; Ilić Tanja M.; Savić Snežana D. (Acta Pharmaceutica)
Two types of biocompatible surfactants were evaluated for their capability to formulate skin-friendly/non-irritant microemulsions as vehicles for two poorly water-soluble model drugs differing in properties and concentrations: alkyl polyglucosides (decyl glucoside and caprylyl/capryl glucoside) and ethoxylated surfactants (glycereth-7-caprylate/ caprate and polysorbate 80). Phase behavior, structural inversion and microemulsion solubilization potential for sertaconazole nitrate and adapalene were found to be highly dependent on the surfactants structure and HLB value. Performed characterization (polarized light microscopy, pH, electrical conductivity, rheological, FTIR and DSC measurements) indicated a formulation containing glycereth- 7-caprylate/caprate as suitable for incorporation of both drugs, whereas alkyl polyglucoside-based systems did not exhibit satisfying solubilization capacity for sertaconazole nitrate. Further, monitored parameters were strongly affected by sertaconazole nitrate incorporation, while they remained almost unchanged in adapalene-loaded vehicles. In addition, results of the in vivo skin performance study supported acceptable tolerability for all investigated formulations, suggesting selected microemulsions as promising carriers worth exploring further for effective skin delivery of model drugs.